Letter from James Curtis Booth to Isaac Lea - Booth, James Curtis (1883)
James Curtis Booth (1810-1888) reminisces with his friend Isaac Lea (1792-1886).
Keywords: Booth, James Curtis, 1810-1888; Lea, Isaac, 1792-1886